Living Space Needs of Small Housing in the Post-Pandemic Era: Malaga as a case study - Cristina Jaime-Segura; Carlos Rosa-Jimenez (Journal of Contemporary Urban Affairs, 2022)
The COVID-19 lockdown period has highlighted the ability of housing to accommodate a comprehensive programme typical of the city and its public space. Housing units of under 60 m2 and in blocks of flats are the more vulnerable, as they have a higher percentage of non-community open spaces. That problem was analysed using a methodology based on psychological, urban planning and architectural indicators applied to two coastal cities in the Mediterranean area of southern Spain. The results highlight three aspects in this type of dwelling: the need to consider the orientation of the housing to improve the quality of indoor and outdoor space; the need in public housing policies for a greater number of rooms to facilitate remote working; and finally, the importance of functional terraces overlooking green areas.